The impact of China’s delayed retirement policy on household allocation of risky financial assets - Liu, Yi; Zhang , Tingting (Transformations In Business & Economics, 2025)
The delayed retirement policy extends households’ expected income periods and reduces precautionary savings, sparking growing academic interest in its broader implications. However, existing literature lacks theoretical insights into how this policy reshapes households’ allocation of risky financial assets. To explore the relationship between delayed retirement policies and households’ allocation of risky financial assets, drawing on the life cycle theory, using the data from the China Household Finance Survey (2011, 2013, 2015, and 2017) and a difference-in-differences model, the impact of China’s delayed retirement policy announcement on household financial asset allocation was analysed. Results reveal that: (1) within the life cycle theory framework, the policy announcement significantly promotes risky financial asset allocation among households in the formation and rearing stages; (2) the policy encourages households with stronger social networks to increase risky asset investments. Risk aversion amplifies the policy’s effect during the formation stage but inhibits it during the rearing stage; (3) the positive impact is more pronounced among urban households, those in eastern China, and highly educated families. This study provides novel insights into implementing progressive delayed retirement policies. Conclusions bridge the theoretical gap regarding how retirement policies shape household risk asset allocation and provide evidence for optimizing policy design through heterogeneity analysis.
Keywords: life cycle theory; delayed retirement policy announcement; household financial asset allocation; family life stages